2009
DOI: 10.1002/jcp.21999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs controlling human ovarian cell proliferation and apoptosis

Abstract: Previous studies have shown that microRNAs (miRNAs) can control steroidogenesis in cultured granulosa cells. In this study we wanted to determine if miRNAs can also affect proliferation and apoptosis in human ovarian cells. The effect of transfection of cultured primary ovarian granulosa cells with 80 different constructs encoding human pre-miRNAs on the expression of the proliferation marker, PCNA, and the apoptosis marker, Bax was evaluated by immunocytochemistry. Eleven out of 80 tested miRNA constructs res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 31 publications
3
134
0
3
Order By: Relevance
“…Whether, physiologically, miR-224, miR-383 and miR-378 are each involved in regulation of aromatase during different stages of follicle development has not been determined. In addition, large-scale functional testing in human granulosa cells revealed effects of multiple miRNAs on the production of progesterone, testosterone and oestradiol, as well as in the expression of the markers of proliferation and apoptosis, PCNA and BAX, although no attempt was made to investigate the mechanisms involved in these responses (Sirotkin et al 2009(Sirotkin et al , 2010.…”
Section: Involvement Of Mirnas During Follicular Growth and Steroidogmentioning
confidence: 99%
“…Whether, physiologically, miR-224, miR-383 and miR-378 are each involved in regulation of aromatase during different stages of follicle development has not been determined. In addition, large-scale functional testing in human granulosa cells revealed effects of multiple miRNAs on the production of progesterone, testosterone and oestradiol, as well as in the expression of the markers of proliferation and apoptosis, PCNA and BAX, although no attempt was made to investigate the mechanisms involved in these responses (Sirotkin et al 2009(Sirotkin et al , 2010.…”
Section: Involvement Of Mirnas During Follicular Growth and Steroidogmentioning
confidence: 99%
“…Increasing evidences on the role of miRNAs during female reproduction point to an association between these molecules and several diseases, which generally affect oocyte developmental competence (Sirotkin et al, 2010;Roth et al, 2014) at least in humans. Although data in domestic animals are not available yet, it is of interest to consider this aspect as well, since it may have a wider impact than currently perceived.…”
Section: Alteration Of Mirna Expression and Implications For Female Fmentioning
confidence: 99%
“…Several studies have indicated the involvement of miRNAs in regulating the proliferation, differentiation, survival, cell cycle transition and/or apoptosis of granulosa cells (Carletti et al, 2010;Sirotkin et al, 2010;Yin et al, 2014;Andreas et al, 2016;Gebremedhn et al, 2016). Interestingly, in vitro granulosa cell culture models have become most popular and widely used to understand the potential role of miRNAs in ovarian functions.…”
Section: Potential Role Of Mirnas In Controlling Ovarian Functionsmentioning
confidence: 99%